Experimental Study of Heat Absorption in Concrete with Paraffin and Beeswax Encapsulated in Plastic Balls as Phase Change Materials - Rejeki Josua Purba, Heri; Amin, Muhammad; Arif, Zainal (Fakultas Teknik Universitas Samudra, 2025)
Energy consumption in the building sector, particularly for air conditioning (AC), accounts for approximately 30% of global energy use and one-third of greenhouse gas emissions. In urban areas, the use of conventional materials such as red bricks and concrete blocks contributes to increased indoor temperatures, thereby raising electricity demand. One promising solution is thermal energy storage technology using Phase Change Materials (PCM). This study presents an experimental investigation of heat absorption in 30×30×15 cm concrete specimens with the addition of paraffin and beeswax PCM encapsulated in plastic balls. The PCM content was varied at 0%, 5%, 10%, and 15% of the concrete volume. Heating was applied using three 160-watt incandescent lamps. The results showed that concrete containing PCM absorbed more heat than the control specimens. Heat absorption by paraffin was 8.19%, 9.83%, and 16.39%, while beeswax achieved 4.91%, 8.19%, and 14.75%. These findings suggest that the use of PCM encapsulated in plastic balls can enhance the thermal energy efficiency of concrete and reduce electricity consumption in buildings.